Focused Ultrasound Promotes the Delivery of Gastrodin and Enhances the Protective Effect on Dopaminergic Neurons in a Mouse Model of Parkinson’s Disease - Wang, Yuhong; Luo, Kaixuan; Li, Junrui; Liao, Yehui; Liao, Chengde; Chen, Wen-Shiang; Chen, Moxian; Ao, Lijuan (Frontiers in Cellular Neuroscience, 2022)
Parkinson's disease (PD) is the second most common chronic neurodegenerative disease globally; however, it lacks effective treatment for this condition at present. Focused ultrasound (FUS) combined with microbubbles could increase the efficacy of drug delivery to specific brain regions and is becoming a promising technology for the treatment of central nervous system diseases. In this study, we explored the therapeutic potential of FUS-mediated blood-brain barrier (BBB) opening to deliver gastrodin (GAS) in a subacute mouse model of PD induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). The concentrations of GAS in the brain was detected by high-intensity liquid chromatography-mass spectrometry (LC-MS) and the distribution of tyrosine hydroxylase (TH) neurons was detected by immunohistochemical staining. The expression of TH, Dopamine transporter (DAT), caspase-3, B-cell lymphoma 2 (Bcl-2), brain-derived neurotrophic factor (BDNF), postsynaptic density protein 95 (PSD-95), and synaptophysin protein were detected by western blotting. Analysis showed that the concentrations of GAS in the brain of PD mice increased by 1.8-fold after the BBB was opened. FUS-mediated GAS delivery provided the best neuroprotective effects and was superior to the GAS or FUS control group. In addition, FUS delivered GAS significantly increased the expression of Bcl-2, BDNF, PSD-95, and synaptophysin protein in the striatum (p < 0.05) and significantly reduced the levels of caspase-3 (p < 0.05). In conclusion, the delivery of FUS can effectively enhance the protective effect of GAS on dopaminergic neurons. This effect may be related to increase of the anti-apoptotic activity and the expression of synaptic-related proteins in the striatum. Data suggest that FUS-enhanced GAS delivery may represent a new strategy for the treatment of PD.